American Sign Language dictionary - Sternberg, Martin L. A. (HarperPerennial, 1998)
An illustrated abridgment of the most authoritative reference book on sign language, with well-written and easily understood instructions for the use of each sign. More than 5,000 signs and 8,000 illustrations. And now includes more than 500 new signs and 1,500 new illustrations. --from publisher.